The Effect Of Work Shift On Subjective Fatigue At PT. Sumber Setia Budi Kolaka Sultra Workers - Arfandi Ahmad; Zulkarnain Alnazar (PT. SAFARI AMALIA, 2022)
PT. Sumber Setia Budi is a company engaged in the nickel mining industry as a contractor partner for the central company PT. Antam Tbk UBPN Sultra is located in Kolaka district, Pomalaa sub-district. The purpose of this study was to determine the effect of work shifts on subjective fatigue in the Mechanic Workshop section using a Cross-Sectional approach with multiple linear regression analysis, the sample amounted to 21 respondents. The instrument used is a Subjective Self Rating Test (SSRT) questionnaire and the types of data are primary and secondary data. The results of the analysis using multiple linear regression with the f test simultaneously show that the significant value and calculated F value between groups of the morning (X1), afternoon (X2), and night (X3) shift simultaneously on subjective fatigue (Y) is F count 2,571 > F table 3.13 and a significant value of 0.229 > 0.05, so it can be concluded that there is an effect between the morning shift (X1), afternoon shift (X2) and night shift (X3) on subjective fatigue but the effect is not significant. To reduce and overcome fatigue experienced by workers, the company should further improve the comfort and facilities of the work environment to create a more comfortable and ergonomic work environment